2009
DOI: 10.1021/ja809051p
|View full text |Cite
|
Sign up to set email alerts
|

Direct Detection of Molecular Biorecognition by Dipole Sensing Mechanism

Abstract: This work investigates the feasibility of transducing molecular-recognition events into a measurable potentiometric signal. It is shown for the first time that biorecognition of acetylcholine (ACh) can be translated to conformational changes in the enzyme, acetylcholine-esterase (AChE), which in turn induces a measurable change in surface potential. Our results show that a highly sensitive detector for ACh can be obtained by the dilute assembly of AChE on a floating gate derived field effect transistor (FG-FET… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 69 publications
0
30
0
Order By: Relevance
“…33 The molecular assembly can be individual molecules, domains of different, maybe even competing, molecules or the cumulative effect of a thin quasi-crystalline film. The chelator-zinc complex, once bound to the PPi, may influence the effective molecular dipole of the chelator such that the effective charge on the surface is positive, decreasing the drain current and producing a negative shift in the threshold voltage of the device, as observed in Figure S1.…”
Section: Resultsmentioning
confidence: 99%
“…33 The molecular assembly can be individual molecules, domains of different, maybe even competing, molecules or the cumulative effect of a thin quasi-crystalline film. The chelator-zinc complex, once bound to the PPi, may influence the effective molecular dipole of the chelator such that the effective charge on the surface is positive, decreasing the drain current and producing a negative shift in the threshold voltage of the device, as observed in Figure S1.…”
Section: Resultsmentioning
confidence: 99%
“…2(a)], the logical gates AND and OR could be readily implemented by a simple combination 5,25,30 of two dipole arrays in approximately defined architectures. 17,19,21,23 In this case, the ligand concentration (in addition to the applied voltage) could modulate the array conductance. 31 The dipole array could also be used as the active layer for a sensor immersed in a solution of a ligand that binds to the molecular dipoles.…”
Section: Resultsmentioning
confidence: 99%
“…The experimental motivation of the proposed nanoswitch is based on the following facts [6][7][8][9][10][11]17,[22][23][24] demonstrated; (iii) local interactions between dipoles are responsible for the observed cooperative phenomena; (iv) promotion or suppression of electron transfer in arrays of molecular dipoles has been reported and attributed to changes in the locally high dipolar electric field (in particular, the dipole moments in molecular junctions dictate the rectification phenomena in the current-voltage curves because it is the relative orientation of the internal dipole field and the externally applied field that controls the junction conductivity); and (v) moderately defective, locally imperfect molecular arrays could still be used in practical nanodevices because of the averaging effects produced by small domains of nanostructures acting cooperatively. In addition, previous theoretical studies have shown significant dipole moment variation 12,13,25 as well as conformational 7,12,26,27 and molecular orbital changes 13,28 that allow tuning the conduction state of molecules with the applied electric field.…”
Section: Physical Modelmentioning
confidence: 99%
“…We hypothesize that the unexpected direction of the sensor response may be caused by a surface dipole effect in which the surface dipole of the chelator is changed only when the immobilized chelator-zinc complex binds to PPi at the surface. 9,12 A control buffer solution without PPi containing the same concentration of zinc does not yield the same effect as exposure to PPi, as shown in Fig. 2b (‘before’ and ‘after’).…”
mentioning
confidence: 86%